2005
DOI: 10.1590/s0100-06832005000300003
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility and ectomycorrhiza formation among Pisolithus Isolates and Eucalyptus spp

Abstract: SUMMARYTwenty-nine isolates of the ectomycorrhiza fungus Pisolithus sp. from different geographical and host origins were tested for their ability to form ectomycorrhizae on Eucalyptus grandis and E. urophylla seedlings under greenhouse conditions. The ectomycorrhiza-forming capacity of isolates varied greatly from one eucalypt species to the other. All isolates from Eucalyptus, nine from Pinus spp. and two isolates from unknown hosts formed mycorrhizae with E. grandis and E. urophylla. Root colonization rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
1
6
0
6
Order By: Relevance
“…are poor colonizers of Eucalyptus spp. (Burgess et al, 1994;Junghans et al, 1998;Pereira et al, 2005). Moreover, in a molecular study of Pisolithus in Kenya, three taxa were identified as occurring only in either pine plantations, eucalyptus plantations or native Afzelia vegetation (Martin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…are poor colonizers of Eucalyptus spp. (Burgess et al, 1994;Junghans et al, 1998;Pereira et al, 2005). Moreover, in a molecular study of Pisolithus in Kenya, three taxa were identified as occurring only in either pine plantations, eucalyptus plantations or native Afzelia vegetation (Martin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A associação ectomicorrízica modifica a arquitetura das raízes (BRUNDRETT, 2008). As hifas geralmente desempenham o papel dos pelos radiculares (SOUZA et al, 2006), os quais estão ausentes em raízes ectomicorrizadas, além disso, estas raízes geralmente são mais curtas e muito ramificadas (RAVEN; EVERT; EICHHORN, 2007). É mais eficiente para a planta, com relação ao gasto de energia, possibilitar maior desenvolvimento de hifas, do que produzir raízes (MOREIRA; SIQUEIRA, 2006).…”
Section: 20% -------------------------------------------------------unclassified
“…Por meio das suas hifas, os fungos aumentam a área de absorção radicular total da planta no solo (MEHARGA; CAIRNEY, 2000; AGARWAL; SAH, 2009) potencializando a absorção de nutrientes e água (SILVA et al, 2003;ANDREAZZA et al, 2004;SMITH;READ, 2008), ciclagem de nutrientes (CAIRNEY, 2012) e aumentando a tolerância das plantas a metais pesados (GRAZZIOTTI; SIQUEIRA; MOREIRA, 2003;KABATA-PENDIAS, 2010). As raízes ectomicorrizadas apresentam manto fúngico cobrindo a superfície de seus ápices e rede de Hartig situado no córtex intercelular, circundando as células epidérmicas e corticais, que substitui a lamela média e possibilita as trocas de nutrientes (BRUNDRETT, 2008;RAVEN;EVERT;EICHHORN, 2007). Uma série de eventos antecede esta modificação da morfologia radicular e para que ocorra a associação o hospedeiro deve possibilitar a infecção pelo propágulo fúngico (MOREIRA; SIQUEIRA, 2006;MARTIN;NEHLS, 2009).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Mean basidiospore diameter (n = 20) was determined for each specimen by measuring from scanning electron micrographs, and basidiospore spine morphology was Pisolithus is often regarded as a cosmopolitan ectomycorrhizal fungus with a wide host range, establishing mycorrhizae with angiosperms and gymnosperms (Marx 1977). However, a great variation in the effects of inoculation with different strains of Pisolithus on the growth of forest trees, as well as compatibility among host and Pisolithus species, has been reported (Burgess et al 1994;Pereira et al 2005). There is considerable polymorphism in terms of morphology and size of Pisolithus basidiomes and spores.…”
mentioning
confidence: 99%